Transient analysis of resonant waveguide devices using a hybrid FETD-GSM algorithm - Kedi Zhang; Jian-Ming Jin; Chao-Fu Wang (Digest - IEEE Antennas and Propagation Society. International Symposium (1995), 2017)
A hybrid algorithm that combines the finite-element time-domain (FETD) method with the generalized scattering matrix (GSM) method is introduced to model resonant waveguide devices. The device is divided into several subdomains with each truncated with the waveguide port boundary condition (WPBC) to suppress resonance and therefore reduce the total number of time-marching steps. The subdomains are analyzed by the FETD method and characterized by broadband GSMs. The GSM of the original device is recovered by cascading the subdomain GSMs. A numerical example is presented to demonstrate the accuracy and efficiency of this algorithm.